FACTORS AND PROSPECTS FOR INCREASING INVESTMENT IN THE GREEN ECONOMY: https://doi.org/10.5281/zenodo.15356748 - Djumayev , Zayniddin (Journal of International science networks, 2025)
This article analyzes the essence of the green economy concept, the necessity of attracting investments to it, the key factors affecting the volume of green investments, and future prospects. Based on global experience, effective methods of financing the green economy and proposals for its development in Uzbekistan are developed.